An Analysis of the Impact of Digitalization and Profit Sharing on the Financial Performance of Brilink Agents at PT Syauqia Berkah Makmur - ALFIAN, Alfian; SIBARANI, Mentiana (International Journal of Environmental, Sustainability, and Social Science, 2025)
This research is based on the importance of operational efficiency and incentive schemes in supporting the financial performance of BRILink agents as part of the micro digital financial services ecosystem. This study aims to analyze the influence of digitalization and profit sharing on agents’ financial performance, both partially and simultaneously. Theoretical concepts discussed include digital transformation, incentive theory, and financial performance based on the balanced scorecard perspective. A quantitative approach with a survey method was used, involving 40 BRILink agents under PT. Syauqia Berkah Makmur. Data were analyzed using multiple linear regression with SPSS version 27. The results indicate that both digitalization and profit sharing have a positive and significant impact on financial performance, either partially or jointly. The coefficient of determination shows that the two variables explain 46.1% of the variation in financial performance. This research concludes that combining technology utilization and a fair profit-sharing system is an effective strategy to improve agent performance.